Diatom Epipelik sebagai Bioindikator Kualitas Perairan Danau Rawa Pening - Soeprobowati, Tri Retnaningsih; Hidayat, Jafron Wasiq; Baskoro, Karyadi (JURNAL SAINS DAN MATEMATIKA, 2011)
Diatom is a unicellular micro algae that had an important role in the food web and major contributor of oxygen in the water. The short life cycle, rapid reproduction, cosmopolite, wide spread distribution, variation in population, most are sensitive to the environmental changes, easily handle samples and identification, low cost ofÂ sampling and data analysis may promote diatoms as a powerful bioindicator of water quality. The unique siliceous frustules make diatoms able to preserve in the sediment. Rawa Pening is a semi natural lake that administratively surrounded by four districts that consist of 27 villages. The main problem of this lake is erosion in the upstream and sedimentation in the downstream area as well as uncontrolled of aquatic plant growth, particularly water hyacinth (Eichornia crassipes) that induce lake shallowness. For people who live around Rawa Pening, this lake had been used for agricultural irrigation, fisheries, electricity power and tourism. To conserve the lake, as 3rd World Water Forum in Tokyo, March 2003 and 2006 â€“ 2009 National Research Agenda there is a need of limnological research on the environmental changes. This research was conducted in order to study the potential used of epipelic diatom as bioindicator of lenthic ecosystem, particularly Rawa Pening Lake. Water and sediment samples were taken from 27 sites from inlet, outlet and water body of Rawa Pining Lake. There were 254 diatom species that consist of 8 Centrophycidae species and 246 Pennatophycidae species. The population varied between 6,989 and 3,781,000 individual/gram. Based on diversity indices of diatom, some part of Rawapening Lake was unstable, whereas the others were stable based on the diversity indices. Based on epipelic diatom, Rawa Pening Lake and its catchments area might be divided into 3 groups: agricultural lotic ecosystem, settlement lotic ecosystem and lenthic ecosystem. The high population of Synedra ulna, Nitzschia palea and Aulacoseira indicated that the lake is eutrophic that tent to be hypereutrophic. It was supported by high concentration of total nitrogen and phosphorous. The concentration of heavy metals Cadmium, Chromium, Copper and Lead were very high in sediment. However, the government of Indonesia has not yet set up sediment quality criteria. The following research would be proposed on this matter. Key words: diatom, bioindicator, water quality, Rawapening